Electrical performance and stability of tungsten indium zinc oxide thin-film transistors - Chauhan, Ram Narayan (2019)
Amorphous tungsten indium zinc oxide thin film transistors (WIZO TFTs) have been prepared using radio-frequency (RF) magnetron co-sputtering system to co-sputter indium zinc oxide (IZO) and indium tungsten oxide (IWO) targets. The electrical performance parameters and positive biased stress (PBS) test of the co-sputtered WIZO TFT were investigated to obtain better characteristics with regards to the IZO and IWO TFT counterparts. The co-sputtered TFT displayed high electrical performance (field effect mobility, µFE ∼ 22.30 cm2/Vs, and sub-threshold swing, SS ∼ 0.36 V/decade) and stable electrical behavior (PBS value shift, ΔVth ∼ 1.23 V) than the IZO (µFE ∼ 19.90 cm2/Vs, SS ∼ 0.46 V/decade, ΔVth ∼ 7.79 V) and IWO (conducting in nature) TFTs for its application in flexible and transparent displays.